50 nm AlxOy ReRAM program 31% energy, 1.6× endurance, and 3.6× speed improvement by advanced cell condition adaptive verify-reset. (January 2015) - Ning, Sheyang; Iwasaki, Tomoko Ogura; Takeuchi, Ken
Highlights: ReRAM program endurance and resistance are compared by changing program conditions. The controlled V reset increment scheme improves 32% program energy and 6.7 times of program speed. The set-before-reset scheme improves 31% program energy, 1.6 times of endurance, and 3.6 times of program speed. Abstract: Two verify-reset schemes are proposed to improve the program energy, endurance and speed of 50 nm Al x O y ReRAM cells. Both of the proposed schemes improve the verify-reset program by adapting the program voltage and pulse width to the variation of ReRAM cell filament status during the verify-reset. In this paper, first, the reset resistance and cell endurance are compared using different reset voltages and reset pulse widths. Then, two proposed verify-reset schemes are introduced independently. The first proposed scheme controlled reset voltage ( V reset ) increment demonstrates 32% program energy reduction and 6.7× program speed increase. In this scheme, the reset voltage stress is increased from −1.5 V to −1.65 V, only when the reset-tries fail continuously during verify-reset (hard-to-reset). The second proposed scheme set-before-reset applies the set pulse during verify-reset, to convert the filament from a hard-to-reset state to an easy-to-reset state. With this approach, 31% program energy reduction, 1.6× program endurance and 3.6× program speed increase can be obtained simultaneously.